Effective Dose to Children during Cardiac Catheterization - Begum, Aleya; Khan, RK; Alam, Kamrul; Hoque, A; Begum, Amena (Bangladesh Journal of Medical Physics, 2013)
The purpose of this study was to assess the effective dose received by children during cardiac procedures. 6 children from 3 to 14 years old who underwent coronary angiogram, cardiac catheterization and pulmonary valvuloplasty treatment were included in the present study. Measurement of effective doses of the paediatric cardiac patients was performed in four catheterization laboratories in three hospitals. Harshaw TLD badges (TLD-100, LiF: Mg, Ti) were used on patients to measure effective dose in the catheterization laboratory. The TLD badges were calibrated from Secondary Standard Dosimetery Laboratory. It is found that the highest dose was 2.01 mSv in 5.4 minute fluoroscopic time during peripheral angiogram and primary pace maker procedure and the lowest effective dose was 0.044 mSv in 1.2 minute fluoroscopic time during coronary angiography performed in the same hospital. The highest fluoroscopic time (18:14 min) was taken to perform a cardiac catheterization and pulmonary valvuloplasty procedure and the dose was 0.781 mSv. During cardiac catheterization children were exposed to high levels of radiation but there was a variant in dosage. Careful consideration should be given to minimize dosage by practicing ALARA principle. This type of study may lead cardiologist and scientist to improve necessary safety measures to be taken to reduce the exposure to patients and occupational worker. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14704 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 145-147